The Impact Of Oral Presentation in Improving Students’ Speaking Ability in Public Jonior High School - Abd Syakur; Agung Budisetyawan; Lailatul Musyarofah; Yulianto Sabat (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
To sustain its future competitive employment both at national and international level, Indonesia Government needs to invest more in its human resources. Therefore,  education  is  the  critical aspect to prepare  highly  educated  and  well-trained  human  resources  for  an  innovation  driven global  competitiveness where ideas are needed to be spoken and trained from earlier age. This study aims to analyse the impact of oral presentation in improving students’ speaking ability in a suburb area in Indonesia. The researcher analyzed how controlled speaking task is able to improve students’ speaking ability in English. The data were collected from SMP Al-Islam Krian Sidoarjo since the school mainly represents the condition of the majority junior high school students in the suburb area in term of teaching and learning situation whom mostly shy and reluctant to show their idea off. While this speaking skill is urgently needed. This study shows that the oral presentation technique is able and effective to help English teachers to solve problems of shy and reluctant students find a way to express their idea spoken.